The Place in the contemporary Algerian short story - Maryam, Bhagibg (Journal of Humanities & Social Sciences, 2018)
Study of the place in the short contemporary Algerian news. Summary of the study: This study has attempted to approach the place of the tale، especially the novelist place. Since the studies take place in the short story on the fingers of the hand، since the place in relation to it is not the most important element to shorten and summarize. Unlike the novel، which is usually a novel places. Indeed، I have tried to extract some places from the historical groups chosen from a period close to time so that I can acquire an integral narrative experience. I relied on a series of books like: the poetic book and place of Gaston Bachelard، the book "the novel and the place" by Yassine Annasser، the book "The place to the Arab novel" by Ghalib Halsa، and the book "business of the novelist place" by Salah Saleh. In reverche we have revised some books that deal with the place in the Algerian short story like: the Algerian revolutionary > Abdullah Rukaibi - critical (the Carpate) "Aourida Abboud the book "The aesthetics of the place in the Algerian short story" by Professor Ahmed Taleb.... And the specific studies instead، remain studies that can not impose a special law for him? As "Gerard Genit" laid a specific law instead and "Philippe Hamon" the law devoted to description and personality whose research remains just individual efforts. This study was as an addition to the specific studies to contemporary Algerian history، considered very rare compared to what door this important element in the creative process، which has managed to deepen such a way in the countryside as a domestic place، which has its value in the construction of narrative artistic work، and who can be one of the fundamental characters. And who can give a view of identifying characters، if not his character himself، and gives the receiving about identifier view، and this through some contemporary Algerian short narratives.
Keywords: the short story; the place; the familiar place; the countryside; the land